Tamarindus indica: Extent of explored potential - Bhadoriya, Santosh Singh; Ganeshpurkar, Aditya; Narwaria, Jitendra; Rai, Gopal; Jain, Alok Pal (Pharmacognosy Reviews)
Tamarindus is a monotypic genus and belongs to the subfamily Caesalpinioideae of the family Leguminosae (Fabaceae), Tamarindus indica L., commonly known as Tamarind tree is one of the most important multipurpose tropical fruit tree species in the Indian subcontinent. Tamarind fruit was at first thought to be produced by an Indian palm, as the name Tamarind comes from a Persian word “Tamar-I-hind,” meaning date of India. Its name "Amlika” in Sanskrit indicates its ancient presence in the country. T.indica is used as traditional medicine in India, Africa, Pakistan, Bangladesh, Nigeria,and most of the tropical countries. It is used traditionally in abdominal pain, diarrhea and dysentery, helminthes infections, wound healing, malaria and fever, constipation, inflammation, cell cytotoxicity, gonorrhea, and eye diseases. It has numerous chemical values and is rich in phytochemicals, and hence the plant is reported to possess antidiabetic activity, antimicrobial activity, antivenomic activity, antioxidant activity, antimalarial activity, hepatoprotective activity, antiasthmatic activity, laxative activity, and anti-hyperlipidemic activity. Every part of the plant from root to leaf tips is useful for human needs. Thus the aim of the present review is to describe its morphology, and explore the phytochemical constituents, commercial utilization of the parts of the plant, and medicinal and pharmacologic activities so that T. indica’s potential as multipurpose tree species can be understood.
Keywords: Antidiabetic; antioxidant; antimicrobial; antiinflammatory; hepatoprotective; Tamarindus indica